Kecanggihan Teknologi Informasi, Partisipasi Manajemen, Dan Pengetahuan Manajer Akuntansi Pada Efektivitas Sistem Informasi Akuntansi (Jurnal Kendali Akuntansi, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence the Effectiveness of Accounting Information Systems, namely Information Technology Sophistication, Management Participation and Knowledge of Accounting Managers, a study of financial management literature. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Information Technology Sophistication affects the Effectiveness of Accounting Information Systems; 2) Management Participation affects the Effectiveness of Accounting Information Systems; and 3) Knowledge of Accounting Managers affects the Effectiveness of Accounting Information Systems.